(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
After Covid-19 was deemed safe, face-to-face learning in the classroom was allowed with the provision that 50% of students could attend school in turn, the rest did online learning. Google classroom is a blended learning platform in education that allows educators to create, share and classify paperless assignments. Google classroom is one of the e-learning applications in history learning. Learning tools that are optimally utilized create effective, efficient learning so that learning objectives can be achieved. History learning is a teaching and learning activity to obtain a shared picture of important events and the state of past societies. This makes the researcher interested in examining further about google classroom. This research uses a qualitative descriptive study method to get an in-depth description and explanation of the implementation of history learning with google classroom as a learning tool at Pasundan 2 Bandung High School. The results of this study show that (1) The selection of google classroom as a learning tool in learning history was chosen because of its ease and effectiveness in use; (2) History learning with google classroom at Pasundan 2 Bandung High School has not been implemented optimally; (3) Students and teachers are not ready for history learning using google classroom so they experience many technical obstacles.